Tetranychus marianae McGregor, 1950 (Acari: Tetranychidae) in Piper (Piperaceae) species in the state of Pará, Brazil - Noronha, Aloyséia C. S.; Menezes, Ilmarina C.; Ferla, Júlia J.; Vieira, Regiane C.; Duarte, Leonardo S.; Mineiro, Jeferson L. C. (Entomological Communications, 2021)
This study reports the occurrence of the phytophagous mite Tetranychus marianae McGregor, 1950 (Tetranychidae), in species of the genus Piper (P. hispidum Sw., P. marginatum Jacq., P. montealegreanum Yunk., P. peltatum L., P. reticulatum L., and P. tuberculatum Jacq.) (Piperaceae) and the predator mite Amblyseius tamatavensis Blommers, 1974 (Phytoseiidae), in species and cultivars of Piper nigrum L., from the Piperaceae collection of Embrapa Amazônia Oriental in Belém, Pará.